Population levels of sport participation: implications for sport policy - R. M. Eime; J. T. Harvey; M. J. Charity; W. R. Payne (BMC, 2016)
Abstract Background Participation in sport can contribute to health-enhancing levels of leisure-time physical activity. There are recent reports that participation in sport in Australia is decreasing. However, these studies are limited to ages 15 years and over. Methods This study integrates sports club membership data from five popular team sports and investigates sport participation across the lifespan (4-100 years) by sex and region (metropolitan/non-metropolitan). Results Overall participant numbers per annum increased from 414,167 in 2010 to 465,403 in 2012 corresponding to a rise in the proportion of Victorian's participating in these sports from 7.5 % in 2010 to 8.3 % in 2012. The highest proportion of participants was in the 10-14 year age range, with participation rates of 36 % in 2010 and 40 % in 2012. There was a considerably lower participation rate in the 15-19 year age group compared to the 10-14 age group, in all three years studied, and the decline continued progressively with increasing age. Male and female age profiles of participation were generally similar in shape, but the female peak at age 10-14 was sharper than for the males, and conversely there were very few 4 year old female participants. Participation rates were generally higher in non-metropolitan than metropolitan areas; the difference increased with increasing age from 4 to 34 years, then steadily declined, reaching parity at around 60 years of age. Conclusions It is a positive sign that participation in these popular sports increased by over 50,000 participants from 2010 to 2012. Large proportions of the population aged 5-14 participate in club based sport. Participation rates decline sharply in late adolescence, particularly for females, and while this may not be a concern from a broad health perspective so long as they transition into other forms of physical activity, it is certainly a matter of concern for the sport sector. It is recommended that sport policy places a higher priority on grass-roots participation and that sporting organisations are supported to prioritise the retention issues occurring during adolescence, particularly for females so as to maximise the potential for sport to maintain its positive contribution to population wellbeing.